1994
DOI: 10.1007/bf02843614
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous administration of Hepatitis B vaccine with other E.P.I. vaccines

Abstract: Development of recombinant DNA vaccine against hepatitis B grown on cultured yeast cell has made it possible to mount a world-wide effort to control and eradicate Hepatitis B infection. However, the currently recommended schedules (0, 1 & 2 months, and 0-1 and 6 months) do not coincide with the scheduled visits for other E.P.I. vaccines, and necessitate additional visits for Hepatitis B vaccination. This study was therefore carried out to find out if adequate seroconversion occurs to Hepatitis B vaccine when g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…2 The recommendation of simultaneous administration is also considered to be an effective strategy for improving the vaccination coverage, acquiring and sustaining the national target of coverage level in other settings. [2][3][4] Extensive clinical practice and experimental evidence showed that administrating all age-appropriate vaccine doses simultaneously is safe and efficacious. [5][6][7] Coverage survey also indicated that failing to give all vaccine doses for which a child is eligible is one of the main reasons for lower coverage.…”
Section: Introductionmentioning
confidence: 99%
“…2 The recommendation of simultaneous administration is also considered to be an effective strategy for improving the vaccination coverage, acquiring and sustaining the national target of coverage level in other settings. [2][3][4] Extensive clinical practice and experimental evidence showed that administrating all age-appropriate vaccine doses simultaneously is safe and efficacious. [5][6][7] Coverage survey also indicated that failing to give all vaccine doses for which a child is eligible is one of the main reasons for lower coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B vaccine was given within 12 hours of birth, then at 6 weeks and at 14 weeks [9]. This is to be noted that the children of Assam in the North-East Region of India have consistently evidenced low rates for routine childhood immunizations.…”
Section: Introductionmentioning
confidence: 99%